2019
DOI: 10.1161/circresaha.118.313835
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Induces Cardiac Lymphangiogenesis After Myocardial Infarction and Regulates Cardiac Edema Via Connexin 43

Abstract: Rationale: Cardiac lymphangiogenesis contributes to the reparative process post myocardial infarction (MI), but the factors and mechanisms regulating it are not well understood. Objective: To determine if epicardial-secreted factor adrenomedullin (AM=protein; Adm=gene) improves cardiac lymphangiogenesis post-MI via lateralization of Connexin43 (Cx43) in cardiac lymphatic vasculature. Methods and Results: Firstly, we identified sex-dependent differences in cardiac lymphatic numbers in uninjured mice using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 74 publications
3
107
0
1
Order By: Relevance
“…Cardiac lymphangiogenesis plays a central role in maintaining fluid homeostasis for healthy heart contraction [18]. Recent studies have suggested that lymphangiogenesis improves cardiac function and healing by draining accumulated fluids and maintaining the physiological interstitial fluid equilibrium [19,20,70]. These studies, together with our RNA sequencing data, suggested that VCFs have a favorable expression of genes related to the regulation of blood and/or lymph vessel formation.…”
Section: Plos Onementioning
confidence: 56%
See 1 more Smart Citation
“…Cardiac lymphangiogenesis plays a central role in maintaining fluid homeostasis for healthy heart contraction [18]. Recent studies have suggested that lymphangiogenesis improves cardiac function and healing by draining accumulated fluids and maintaining the physiological interstitial fluid equilibrium [19,20,70]. These studies, together with our RNA sequencing data, suggested that VCFs have a favorable expression of genes related to the regulation of blood and/or lymph vessel formation.…”
Section: Plos Onementioning
confidence: 56%
“…In this study, VCF treatment appeared to efficiently mobilize LECs in the infarct zone (Fig 6), but there was no significant difference between the VCF and control groups in the extent of fibrosis (Fig 5). Similarly, Trincot et al reported that adrenomedullin overexpression induces mouse cardiac lymphangiogenesis after myocardial infarction, but the area of fibrosis is not changed [70]. Although further studies are necessary to understand the relations between lymphangiogenesis and fibrosis, regulatory T cells seems involved as they have been shown to improve cardiac function after myocardial infarction via the inhibition of inflammation and the attenuation of interstitial fibrosis [16,77].…”
Section: Plos Onementioning
confidence: 97%
“…[7] Studies have reported that the elevation of Cx43 could effectively reduce ventricular arrhythmias in MI model due to increased conduction velocity and intercellular coupling. [9,38,39] Trincot et al [18] reported that increased gap junction coupling induced by Cx43 between human lymphatic endothelial cells helped endogenous lymphangiogenic response that preserve cardiac function and reduce oedema after MI. Here, we demonstrated that overexpression of miR-1 abolished metoprolol's effect on enhancing intercellular communication, which may be attributed to inhibition of Cx43.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Cx43 has been identified as a direct target of miR-1 [16] and is proved as a key therapeutic target in ischaemia/reperfusion injury [17] as well as MI. [18] Here, we determined the effects of b1-blocker metoprolol on expression of miR-1 and Cx43 in heart tissue of MI rats. As shown in Figure 3a and b, miR-1 expression was remarkably up-regulated while Cx43 was down-regulated in MI group.…”
Section: Metoprolol Decreases Mir-1 and Increases Cx43 In Heart Tissumentioning
confidence: 99%
“…Of all currently identified connexin genes, connexin 43 is the most extensively expressed and has been investigated in the most detail. [6][7][8] Connexin 43 observed in RPE 4,9 is capable of mediating intercellular dye transfer 4 and protecting against oxidative stress-induced cell death. 9 Zona occludens 1 (ZO-1) was one of the first recognized and best-studied tight junction proteins.…”
mentioning
confidence: 99%